Ibsen's two versions of The burial mound. A comparison of the stage directions of the two versions of the play - Gjervan, Ellen Karoline (Nordlit, 2015)
In this article I compare and discuss the differing stage directions of the two versions of Ibsen’s play The Burial Mound. Furthermore, I explore how the variance regarding the stage directions of the two versions of the play can be explained by Ibsen’s increased theatre affinity, due to his work as stage director and stage manager at the theatre in Bergen during the early 1850s.
Keywords: Stage directions; Ibsen as a practical man of the theatre; theatrical space; the 1850s theatre culture; Det norske Theater in Bergen.